COMPARATIVE STUDY ON ULTIMATE TENSILE STRENGTH OF SOME T-SHAPE CORNER JOINTS OF STRUCTURAL ELEMENTS OF SOLID BEECH WOOD WITH CROSS SECTION OF 50 x 25 mm - Kyuchukov, Borislav; Kyuchukov, Georgi; Jivkov, Vassil (Innovation in Woodworking Industry and Engineering design, 2014)
In this work, the ultimate tensile strength of some T-shape corner joints of structural ele-ments of solid beech wood with cross section 50 x 25 mm used in the construction of seating furniture is investigated. It has been found that with reference to the value of ultimate tensile strength, the glued T-shape corner joints are arranged in the following descending series: with stub mortise and tenon; with wedged mortise and tenon; with stub mortise and tenon and dowel, with dowels. With reference to the value of the ultimate tensile strength the dismountable end corner joints are arranged in the following descending series: with two connectors with screw and cross dowel; with two one-piece connectors “Confirmat”. It is recommended that the results from this research can be utilized when calculating the dimensions of seating furniture.